2015
DOI: 10.1016/j.psep.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A study of the precursors leading to ‘organisational’ accidents in complex industrial settings

Abstract: It is argued that organisational vulnerability tools should be developed to enable a systematic approach to 'diagnosing' incubating precursors. It is also argued that there is the potential for 2 further resilience to be achieved through the use of models of the complex dynamics of sociotechnical processes within organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Previous work at Bristol University, initiated by British Nuclear Fuels and funded by the UK Nuclear Installations Inspectorate (now the Office for Nuclear Regulation), studied the organisational and cultural precursors that underlie the more easily identifiable causes of engineering disasters (Taylor et al, 2015). This drew on the findings of an earlier industry study (Taylor and Rycraft, 2004).…”
Section: Previous Research At the Safety Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work at Bristol University, initiated by British Nuclear Fuels and funded by the UK Nuclear Installations Inspectorate (now the Office for Nuclear Regulation), studied the organisational and cultural precursors that underlie the more easily identifiable causes of engineering disasters (Taylor et al, 2015). This drew on the findings of an earlier industry study (Taylor and Rycraft, 2004).…”
Section: Previous Research At the Safety Systemsmentioning
confidence: 99%
“…These were The published investigation reports on these events on which the studies were based (references to the relevant reports and the methodology used are given by Taylor et al (2015)) repeatedly reached conclusions which showed that failures were attributable to very similar organisational and cultural weaknesses, suggesting that if defences could be developed, they would have wide applicability.…”
Section: Previous Research At the Safety Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decentralised WW system are simpler and cost effective referring to centralised WW system which needs large capital investment for sewer system and pumping costs, > 70% of total annual budget [14][15][16].…”
Section: Characteristics For the Studied Urban And Industrial Wws Manmentioning
confidence: 99%
“…The disastrous consequences that SA failures (e.g. missing indicators) can through poor decision making and unnecessary risk taking have been recognised in process safety (Kaber & Endsley, 1998;Taylor, Wijk, May & Carhart, 2015) (e.g. Deepwater Horizon; Roberts et al, 2015b;Texas City;Khan & Amyotte, 2007; explosion at the chemical production facility West Virginia Institute, Naderpour, Nazir & Lou, 2015).…”
Section: Situation Awarenessmentioning
confidence: 99%